Does sodium citrate cause the same ergogenic effect as sodium bicarbonate on swimming performance? - Kumstát, M.; Hlinský, T.; Struhár, I.; Thomas, A. (Journal of Human Kinetics, 2018)
The aim of this study was to investigate the effect of ingesting sodium bicarbonate (SB) and sodium citrate (SC) on 400 m high-intensity swimming performance and blood responses. Six nationally ranked male swimmers (20.7 ± 2.1 yrs; 184 ± 6 cm; 79.9 ± 3.9 kg; 10.6 ± 1% body fat) participated in a double blinded, placebo controlled crossover trial. Ninety minutes after consuming SB (0.3 g·kg-1), SC (0.3 g·kg-1) or a placebo (PL) participants completed a single 400-m freestyle maximal test on three consecutive days. The order of the supplementation was randomized. Capillary blood samples were collected on 4 occasions: at rest (baseline), 60 min post-ingestion, immediately post-trial and 15 min post-trial. Blood pH, HCO3- concentration and base excess (BE) were determined. Blood pH, HCO3-, BE were significantly elevated from before loading to the pre-test (60 min post-ingestion) (p < 0.05) after SB ingestion, but not after SC ingestion (p > 0.05). Performance times were improved by 0.6% (p > 0.05) after supplementation of SB over PL in 5 out of 6 participants (responders). In contrast, ingestion of SC decreased performance by 0.2% (p > 0.05). No side effects were observed in either trial. Delayed blood response was observed after SC ingestion compared to SB and this provided no or modest ergogenic effect, respectively, for single bout high-intensity swimming exercise. Monitoring the magnitude of the time-to-peak level rise in alkalosis may be recommended in order to individualize the loading time accordingly before commencement of exercise.